2017
DOI: 10.4997/jrcpe.2017.108
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Dysfunction in Parkinson'S Disease

Abstract: Respiratory dysfunction has been associated with Parkinson's disease since it was first described in 1817. The respiratory symptoms observed in Parkinson's disease patients vary greatly. Most patients remain asymptomatic, whereas others present with acute shortness of breath and even stridor.In August 2016, an electronic literature search was conducted using PubMed and Google Scholar. Results were screened and studies reporting on respiratory dysfunction associated with Parkinson's disease were included.Respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 30 publications
3
48
0
6
Order By: Relevance
“…However, a restrictive pattern of pulmonary dysfunction has been a consistent finding, reported in up to 94% of cases in different studies. This has been attributed to a combination of factors including increased rigidity of the respiratory muscles and chest wall, and reduced lung volumes because of kyphoscoliosis . The response to levodopa in patients with restrictive deficits has been variable, with improved pulmonary function demonstrated in some studies but not in others.…”
Section: Studies Of Pulmonary Function In Pdmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a restrictive pattern of pulmonary dysfunction has been a consistent finding, reported in up to 94% of cases in different studies. This has been attributed to a combination of factors including increased rigidity of the respiratory muscles and chest wall, and reduced lung volumes because of kyphoscoliosis . The response to levodopa in patients with restrictive deficits has been variable, with improved pulmonary function demonstrated in some studies but not in others.…”
Section: Studies Of Pulmonary Function In Pdmentioning
confidence: 99%
“…For example, the term “sensory dyspnea” has been used in PD to refer to the feeling of inability to take a breath in the absence of observable abnormal breathing. These observations lead to further questions regarding the contribution to the genesis of dyspnea of subjective sensory and perceptual changes, such as the threshold for dyspnea and the perception of respiratory load, which have so far received limited attention and warrant further investigation …”
Section: Future Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The lungs are one of the most sensitive organs in the body; however, few studies have described the negative changes and impact on the lungs during the development of PD (Baille et al, 2018;Seccombe et al, 2011;Torsney & Forsyth, 2017).…”
Section: Impairment Of Lung Properties In Pd Micementioning
confidence: 99%
“…Breathing problems are recognized as a cause of morbidity and mortality in patients with Parkinson's disease (PD), caused by neural damage in specific regions of the ventral medulla that are responsible for rhythm generation and chemoreception, such as the preBötzinger complex (preBötC) and retrotrapezoid nucleus (RTN), respectively (Baille et al., ; Benarroch, Schmeichel, Low, & Parisi, ; Owolabi, Nagoda, & Babashani, ; Seccombe et al., ; Torsney & Forsyth, ). Previous studies have also found that PD patients showed a reduction of pulmonary volumes and stiffening of respiratory muscles, indicating an impairment directly in the lung, ribcage and/or the muscles responsible for breathing (Baille et al., ; LeWitt et al., ; Owolabi et al., ; Seccombe et al., ).…”
Section: Introductionmentioning
confidence: 99%